Midterm 7 Solutions

# Nb where h t y h0l 1 y h0l 1 2 h

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Âwt 2 0\ + Â ‰ So now we calculate Xx 0\ and Xx 1\, using - ¬༼ ‰ - ` ÂH t — 3Âwt 2 1\F Printed by Mathematica for Students 1 n\ = ‰ -Â w t Jn + N 2 n\ 3 YHx, tL = Xx yHtL\ = Xx ‰ 4 ` ÂH t - y H0L\ — MidtermExam7Solutions.nb where ‰ - ‰ - ` ÂH t — y H0L\ = 1 y H0L\ = 1 2 ` ÂH t — ‰ - B‰ 2 ` ÂH t B 0\ + Â 1\F — Âwt - 0\ + Â ‰ 2 - ¬༼ ‰ - ` ÂH t — 1 n\ = ‰ -Â w t Jn + N 2 n\ 3Âwt 1\F 2 So now we calculate Xx 0\ and Xx 1\, using ` a 0] = 0 ` Yx a 0] = 0 ` Xx Ix + mw 2— ` ¬༼ a = ` px M 0\ = 0 Â mw „ „x mw — Xx 0\ = A ‰ - ` Ix + Â mw ` px M ` Yx x 0] = x Xx 0\ ` „ Yx px 0] = -Â — „ x Xx 0\ ¬༼ Xx 0\ = - mw 2— x Xx 0\ m w x2 2— where A is imposed by normalization ¶ 2 Ÿ-¶ Xx 0\ A ¶ 2 Ÿ-¶ ‰ - ¶ p — 1ê 2 ImwM 2 ¬༼ Ÿ-¶ ‰- b x = „x = 1 — 2 A „x = 1 m w x2 pê b ; b = ¬༼ Choose A œ Rཻ, therefore =1 m w 1ê4 A = I p— M Thus m w 1ê4 X x 0\ = I p — M ‰ - m w x2 2— We calculate Xx 1\ by applying the raising operator `† a 0^ = ` Xx Ix - mw 2— mw 2— m w 1ê4 I p— M Ix - Â mw —„ M‰ m w „x `† ¬༼ a = 1^ ` px M 0\ = Xx 1\ m w x2 = Xx 1\ 2— therefore...
View Full Document

## This note was uploaded on 02/01/2014 for the course PHYC 491/496 taught by Professor Akimasamiyake during the Fall '13 term at New Mexico.

Ask a homework question - tutors are online